Efecto de la precipitación sobre la dinámica hidrológica de las lagunas de la cuenca inferior del Río Colorado (período 1981-2011) - Aliaga, Vanina Solange (2014)
The purpose of this study was to analyze the temporal dynamics of shallow lakes during the 2002-2012 years in the Colorado River Basin in relation to climate variability. Dry and humid periods were identified by water balance. Moreover, the inﬂuence of the extreme rainfall events on the shallow lakes in the region was analyzed. Shallow lakes area was estimated during three different years by satellite image processing (LANDSAT 5TM y 7 ETM). Water bodies were classified according to geomorphological, hydrological and morphometric criteria during a normal period. According rainfall amounts, 2011, 2004 and 2008 were considered normal, wet and dry years, respectively. As a result, 15 (normal), 20 (wet), and 5 (dry) shallow lakes which covered an area of 13.05, 14.54, and 5.8 km2 respectively were detected. A correlation between the area covered by water and the annual precipitation was obtained in the study area. As a result of the clustering method application, 3 groups of water bodies were defined. The first included the biggest and permanent water bodies (area > 1.5 km2). Group 2 included salt shallow lakes which Total Maximum Length (TML) orientation was N-S. The remaining group was composed by lakes located in the wettest area of the basin with an E-W LMT orientation.